2022
DOI: 10.4103/jcvjs.jcvjs_104_22
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional area of the longus colli and cervical degenerative spondylolisthesis

Abstract: Background: Limited literature is available to define the impact of the longus colli muscle, a deep flexor of the spine, on cervical spine stability despite its close proximity to the vertebrae. Aims and Objectives: The purpose of this study was to determine if longus colli cross-sectional area (CSA) is associated with the severity preoperative cervical degenerative spondylolisthesis. Materials and Methods: Patients undergoing elective anteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Second, different studies demonstrated a correlation between muscle degeneration, chronic neck pain and disability. [19][20][21] Moreover, avoidance behavior could potentially lead to disuse-based atrophy and further complicate this self-propagating cycle of pain. 22 The hypertrophy of the PL muscle group has several different explanations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, different studies demonstrated a correlation between muscle degeneration, chronic neck pain and disability. [19][20][21] Moreover, avoidance behavior could potentially lead to disuse-based atrophy and further complicate this self-propagating cycle of pain. 22 The hypertrophy of the PL muscle group has several different explanations.…”
Section: Discussionmentioning
confidence: 99%
“…The anterior muscles are no longer needed for this function and atrophy from disuse. Second, different studies demonstrated a correlation between muscle degeneration, chronic neck pain and disability 19–21 . Moreover, avoidance behavior could potentially lead to disuse-based atrophy and further complicate this self-propagating cycle of pain 22 …”
Section: Discussionmentioning
confidence: 99%